Una mirada retrospectiva a la informalidad en Bogotá - Mendoza, Pilar (Pontificia Universidad Católica del Perú, 2015)
Heavy civil riots occurred in Bogota on April 9th, 1948, the day when the popularleader Jorge Eliecer Gaitan was killed. This popular insurrection had deep consequences which reflect to the present-day construction of the city. Crowds of people from the popular districts of the city took part in demonstrations that resulted in the death of about 3,000 people and destroyed parts of the historic center and some symbolic places. Subsequently, the rebellion spread throughout the whole country. After this historic event, which is known as the ‘Bogotazo’, the modernization, which had started beforehand, sped up in a radical way. At the same time, the ingression of new inhabi- tants from the surrounding region increased significantly, resulting in Bogota developing into the metropolis it is today. The poor and working class population started with the invasion and the construction of ‘pirate quarters’ in the southern suburban area and in the eastern hills, while the rich population started moving toward the north of the city. In this way, the suburbs seem to be a projection of the city but in a rather unplanned way, which have mainly been generated by the population itself. In this way we describe the process in which working class people took possession of a large city, and the way in which a city was informally developed, resulting in the creation of suburban quarters.

El 9 de abril de 1948, día del asesinato del líder popular Jorge Eliecer Gaitan, se produjo enBogotá una revuelta popular de profundas consecuencias. Este evento definió en parte la manera en la que se construyó la ciudad desde entonces. Gente de toda Bogotá, incluidos los barrios populares, descendió al centro histórico (lugar del asesinato) para unirse a las manifestaciones que provocaron la muerte de aproximadamente 3000 personas y la semi-destrución de algunos lugares simbólicos. Dicha revuelta se extendió a todas las regiones del país.Después de dicho acontecimiento, conocido como El Bogotazo, la modernización de la ciudad que ya había comenzado se acentuó de manera radical. Paralelamente, la entrada masiva de habitantes de todo el país le dio a Bogotá la connotación de metrópoli. Las clases populares comenzaron la invasión de las periferias con la construcción de ‘barrios piratas’ hacia el sur de laciudad, mientras que los ricos se dirigieron al norte. De esta manera, la periferia surgió como una proyección de la ciudad, pero de una manera no planificada y autogestionada por la población. Describiremos en este articulo la manera en que los sectores populares se apropian de la gran ciudad y la dotan de identidad, en la medida en que la informalidad y la distancia con el sistema oficial se convierten en la forma efectiva de definir un territorio en la ciudad.
A retrospective view of informalilty in Bogota
Keywords: Politics; Bogotazo; Modernization; Working Class Population; Suburban Quarters; Bogotazo; Modernización; Sectores Populares; Barrios Periféricos; https://purl.org/pe-repo/ocde/ford#5.06.00